High‐efficiency production of bisabolene from waste cooking oil by metabolically engineered Yarrowia lipolytica - Yakun Zhao (Wiley, 2021)
Summary The natural plant product bisabolene serves as a precursor for the production of a wide range of industrially relevant chemicals. However, the low abundance of bisabolene in plants renders its isolation from plant sources non‐economically viable. Therefore, creation of microbial cell factories for bisabolene production supported by synthetic biology and metabolic engineering strategies presents a more competitive and environmentally sustainable method for industrial production of bisabolene. In this proof‐of‐principle study, for the first time, we engineered the oleaginous yeast Yarrowia lipolytica to produce α‐bisabolene, β‐bisabolene and γ‐bisabolene through heterologous expression of the α‐bisabolene synthase from Abies grandis, the β‐bisabolene synthase gene from Zingiber officinale and the γ‐bisabolene synthase gene from Helianthus annuus respectively. Subsequently, two metabolic engineering approaches, including overexpression of the endogenous mevalonate pathway genes and introduction of heterologous multidrug efflux transporters, were employed in order to improve bisabolene production. Furthermore, the fermentation conditions were optimized to maximize bisabolene production by the engineered Y. lipolytica strains from glucose. Finally, we explored the potential of the engineered Y. lipolytica strains for bisabolene production from the waste cooking oil. To our knowledge, this is the first report of bisabolene production in Y. lipolytica using metabolic engineering strategies. These findings provide valuable insights into the engineering of Y. lipolytica for a higher‐level production of bisabolene and its utilization in converting waste cooking oil into various industrially valuable products.